Peran Guru dalam Mempersiapkan Manajemen Sumber Daya Manusia di Era Society 5.0 (Studi Kasus Generasi Alpha) - Pesa Nugraha, Putu; Dedi Sulaiman (Madaniyah, 2024)
In the era of Society 5.0, where technology and human interaction are increasingly integrated, human resource management (HRM) is crucial for organizational success. Teachers play a vital role in preparing Generation Alpha to face future challenges by acting as facilitators in developing essential skills such as social abilities, problem-solving, critical thinking, and creativity. They also help students understand technological advancements and their impact on future job markets. This study, using a qualitative case study method, focuses on the role of teachers in preparing HRM for Society 5.0. Findings highlight that teachers are key in identifying student potential, nurturing talent, and preparing students for future jobs that do not yet exist. Teachers also play a significant role in instilling positive work attitudes, including work ethics, responsibility, collaboration, and leadership. Additionally, they help students understand the importance of diversity and inclusivity in an increasingly global workplace. The research emphasizes the need for education to evolve and stay relevant in the face of Society 5.0 challenges. Continuous development for teachers and collaboration between government, educational institutions, and industry are essential to ensure that school curricula align with future workforce needs. Keywords: Teacher, human resource management, Society 5.0, Generation Alpha, education.